Data Governance Blueprint For Online Learning: A Case Study On Tutor LMS And Wordpress - Tomi Yulianto; Heru Purnomo; Mohammad Achmad (Jurnal Mamangan, 2024)
Data management and governance play a vital role in ensuring the successful implementation of information systems in organizations, especially in online learning platforms based on Tutor LMS on WordPress. This article discusses the development of a data framework (data blueprint) through a case study approach to an e-learning platform that includes four main phases: Data Strategy and Maturity, Data Integration Assessment, Data Quality Assessment, and Data Analytics Evaluation. By implementing appropriate data governance principles, such as role-based access control (RBAC), API integration, and data quality validation, the platform can provide a more adaptive, efficient, and secure learning experience. This article aims to contribute to the practical and theoretical understanding of modern data management in technology-based education environments. The implementation of structured data governance through a data blueprint approach can improve the effectiveness, efficiency, and security of online learning systems. The four main phases—data strategy, integration, quality, and analytics—are the foundation for managing data as a strategic asset. The support of advanced technologies such as APIs, AI, and visual dashboards facilitate accurate and real-time data-based decision making.